Analyzing Civil-Military Response in Pakistan’s Counter-Terrorism Efforts (2014–2016) (Journal of Social Sciences Review, 2025)
The study attempts to evaluate the civil-military response in Pakistan's counter-terrorism efforts between 2014 and 2016 as this period was characterized by significant security challenges and decisive state actions. It commences by examining the government's strategic shift in 2014 in response to the escalation of terrorist activities, particularly the Army Public School (APS) Peshawar attack, which marked a critical turning point in civil-military cooperation. The research investigates into the complex relationship between state politics and the rising threat of terrorism, with a particular emphasis on the All-Parties Conference and the development of the 20-point National Action Plan (NAP) that facilitated the cultivation of political consensus. It also examines Pakistan's diplomatic interactions, particularly with Afghanistan, which are designed to promote regional harmony. Operation Zarb-e-Azb (2014–2016) is a critical component of this period, emphasizing the military's operational leadership and collaboration with civilian authorities. By evaluating strategic diplomacy, operational measures, and policy decisions, the article assesses the efficacy and constraints of the civil-military nexus. The results indicate that while cooperation enhanced national security outcomes, long-term counterterrorism success necessitates democratic oversight, inclusive political will, and sustained institutional alignment.
Keywords: Terrorism; Civil-Military Cooperation; Zarb-e-Azb; National Action Plan (NAP); Pakistan; Afghanistan